Exploring the causal relationship between gastroesophageal reflux and oral lesions: A mendelian randomization study - Shu, Linjing; Tong, Xu (Frontiers in Genetics, 2022)
BACKGROUND: Clinical observations and retrospective studies have observed that patients with gastroesophageal reflux disease (GERD) have an increased probability of dental erosion, periodontitis and oral mucosal lesions and other common oral lesions. However, whether there is a genetic causal relationship between GERD and the occurrence of oral lesions has not been reported. Methods: In this study, we extracted instrumental variables from the largest published summary statistics of the oral lesion phenotype GWAS in UK Biobank (UKBB) and GERD GWAS. Then, we performed a causal inference analysis between GERD and common oral lesions by mendelian randomization analysis with the R package “TwoSampleMR”. Results: We observed a significant causal relationship between GERD and several common oral lesion phenotypes (painful gums, loose teeth, toothache, and mouth ulcers). GERD showed a positive correlation with the occurrence of these oral lesions. After removing outlier SNPs via the MR-PRESSO package, our conclusions were still robust. Conclusions: Our findings provide the first evidence for a genetic causal effect of GERD on oral lesion pathogenesis. For patients with confirmed GERD, attention should be paid to taking interventions to prevent the occurrence of oral lesions.